Expression of phosphorylated high molecular weight neurofilament protein (NF-H) and vimentin in human developing dorsal root ganglia and spinal cord - Lukás, Z; Dráber, P; Bucek, J; Dráberová, E; Viklický, V; Dolezel, S (Histochemistry, 1993)
The expression of vimentin and the phosphorylated variant of high molecular weight neurofilament protein (NF-H) was studied in developing human fetal dorsal root ganglia and spinal cord. The technique used for examination of cryosections was double-label fluorescence with monoclonal antibodies. Both proteins were present in the nerve fibres inside the ganglia of 6- and 8-week-old embryos. During further development the expression of vimentin continued to increase in the satellite cells, but was found to be decreasing in the ganglion cells. Phosphorylated NF-H was found in the processes of ganglion cells, as well as in the perikarya at all developmental stages. In the spinal cord of 6- and 8-week-old embryos, phosphorylated NF-H protein was found in the longitudinal fibres of the marginal layer and in processes of the mantle zone; some of the fibres also contained vimentin. Later the co-expression of the two proteins ceased and vimentin was found only in glial and mesenchymal derivatives. Phosphorylated NF-H was located, at all developmental stages, in the axons of both white and grey matter, but not in the neuronal perikarya. The results indicate that phosphorylation of the NF-H in human dorsal root ganglia starts in the perikarya of the ganglion cells while in the ganglion cells of the spinal cord it takes place in the axons.
Keywords: Phosphorylation; neurofilamentové proteiny; Humans; Intermediate Filament Proteins; fosforylace; Spinal Cord; molekulová hmotnost; Antibody Specificity; Neurofilament Proteins; gestační stáří; Antibodies, Monoclonal; mícha; spinální ganglia; lidé; proteiny intermediálních filament; Vimentin; specificita protilátek; monoklonální protilátky; Ganglia, Spinal; Gestational Age; vimentin; Molecular Weight